Serum Homocysteine Levels in Men with and without Erectile Dysfunction: A Systematic Review and Meta-Analysis - Andrea Sansone; Angelo Cignarelli; Massimiliano Sansone; Francesco Romanelli; Giovanni Corona; Daniele Gianfrilli; Andrea Isidori; Francesco Giorgino; Andrea Lenzi (International Journal of Endocrinology)
Objectives. Elevated levels of serum homocysteine (Hcy) have been associated with cardiovascular diseases and endothelial dysfunction, conditions closely associated with erectile dysfunction (ED). This meta-analysis was aimed to assess serum Hcy levels in subjects with ED compared to controls in order to clarify the role of Hcy in the pathogenesis of ED. Methods. Medline, Embase, and the Cochrane Library were searched for publications investigating the possible association between ED and Hcy. Results were restricted by language, but no time restriction was applied. Standardized mean difference (SMD) was obtained by random effect models. Results. A total of 9 studies were included in the analysis with a total of 1320 subjects (489 subjects with ED; 831 subjects without ED). Pooled estimate was in favor of increased Hcy in subjects with ED with a SMD of 1.00, 95% CI 0.65–1.35, p<0.0001. Subgroup analysis based on prevalence of diabetes showed significantly higher SMD in subjects without diabetes (1.34 (95% CI 1.08–1.60)) compared to subjects with diabetes (0.68 (95% CI 0.39–0.97), p<0.0025 versus subgroup w/o diabetes). Conclusions. Results from our meta-analysis suggest that increased levels of serum Hcy are more often observed in subjects with ED; however, increase in Hcy is less evident in diabetic compared to nondiabetic subjects. This study is registered with Prospero registration number CRD42018087558.